2006
DOI: 10.1029/2005je002491
|View full text |Cite
|
Sign up to set email alerts
|

Gusev crater: Wind‐related features and processes observed by the Mars Exploration Rover Spirit

Abstract: [1] Wind-related features observed by the rover Spirit in Gusev crater, Mars, include patches of soil on the surface, some of which are organized into bed forms. Windblown grains include dust (inferred to be <3 mm in diameter), sands (up to a few hundred mm in diameter), and granules (>2 mm in diameter). Microscopic Imager data show the sands and granules to be rounded and relatively spherical, typical of grains transported long distances by the wind. The interior of bed forms exposed by rover operations sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
160
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(169 citation statements)
references
References 64 publications
9
160
0
Order By: Relevance
“…Vortexes in the atmosphere are capable of lifting dust, which is typically "bright," into the atmosphere, leaving coarser grained materials on the surface, which then appear comparatively dark. Spirit MI images show that soils within such a "dark" streak are relatively free of dust, whereas Mi images outside the streak appear dustier, confirming this model (Greeley et al, 2005(Greeley et al, , 2006a.…”
Section: Geomorphologysupporting
confidence: 68%
“…Vortexes in the atmosphere are capable of lifting dust, which is typically "bright," into the atmosphere, leaving coarser grained materials on the surface, which then appear comparatively dark. Spirit MI images show that soils within such a "dark" streak are relatively free of dust, whereas Mi images outside the streak appear dustier, confirming this model (Greeley et al, 2005(Greeley et al, , 2006a.…”
Section: Geomorphologysupporting
confidence: 68%
“…Thermal inertia data from space-borne imagery of Mars indicates that Martian dunes have an average grain size that is coarser (medium-to coarsegrained sand) than on Earth Christensen 1991, Presley andChristensen 1997). Limited surface observations (e.g., Gusev Crater by Greeley et al [2006] and Sullivan et al [2008]; Meridiani Planum by Jerolmack et al [2006]) indicate eolian sands that are similar in size or slightly finer than those on Earth.…”
Section: Marsmentioning
confidence: 99%
“…The Mars Exploration Rover Opportunity found that the regolith in the Meridiani region was a poorly sorted mix of fine basaltic sand and hematite granule-sized concretion fragments (Sullivan et al, 2005), and the Spirit rover also observed granule-coated ripples where the granules were comprised of rounded rock fragments (Greeley et al, , 2006. Where the regolith was worked into ripples, a monolayer of fragments was often seen on the ripple crests, with basaltic sands on the flanks, and whole concretions or other clasts mixed with basaltic sands in the inter-ripple zones.…”
Section: Age and Bedform Mobilitymentioning
confidence: 99%